2014
DOI: 10.1002/qj.2405
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for simultaneous retrieval of ice and liquid water cloud properties. Part I: Information content and case study

Abstract: This article presents a novel methodology dedicated to retrieving the optical and microphysical properties of ice and liquid water clouds simultaneously. An optimal estimation method is used to retrieve the ice water path of one ice-cloud layer and the optical thickness and droplet effective radius of up to two liquid-water cloud layers, along with rigorous uncertainties. In order to perform the retrievals, radiometric measurements in five channels ranging from the visible to the thermal infrared are utilized.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 65 publications
1
58
0
Order By: Relevance
“…Forward simulations of upward radiance have been performed by 1-D radiative transfer simulations using the radiative transfer package LibRadtran 2.0 (Mayer, 2005;Emde et al, 2016), the discrete ordinate radiative transfer solver (DISORT) version 2 (Stamnes et al, 2000), and assuming ↑ M,λ for the cirrus (ci) and DCC case. η is the mean standard deviation with the subscripts "S" for SMART and "M" for MODIS.…”
Section: Radiance Ratio Retrieval and Uncertainty Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Forward simulations of upward radiance have been performed by 1-D radiative transfer simulations using the radiative transfer package LibRadtran 2.0 (Mayer, 2005;Emde et al, 2016), the discrete ordinate radiative transfer solver (DISORT) version 2 (Stamnes et al, 2000), and assuming ↑ M,λ for the cirrus (ci) and DCC case. η is the mean standard deviation with the subscripts "S" for SMART and "M" for MODIS.…”
Section: Radiance Ratio Retrieval and Uncertainty Estimationmentioning
confidence: 99%
“…However, studies by Hahn et al (1984) and Warren et al (1985) analyzing ground-based observations reported that the coexistence of multilayer clouds (e.g., cirrus above liquid water clouds) is found in about 50 % of the cases. Chang and Li (2005) and Sourdeval et al (2015) have demonstrated that omitting the low liquid water cloud in the retrieval algorithm introduces significant uncertainties in the retrieved cirrus properties.…”
Section: Introductionmentioning
confidence: 99%
“…King et al, 1998;Sourdeval et al, 2013). Direct retrievals of the vertically integrated ice water content (IWC) -the ice water path (IWP) -can also be obtained from these channels (Sourdeval et al, 2015), passive microwave sensors (Gong and Wu, 2014), or a synergy of both (Holl et al, 2014). Vertical profiles of the cloud visible extinction (α ext ), IWC and ice crystal r eff are 10 commonly provided using lidar and/or radar measurements (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancies among climate models (Waliser et al, 2009) in terms of ice water path (IWP) indicate that the GCM parameterizations need more reliable constraints on IWP. Recent work by Sourdeval et al (2015), which includes direct retrieval of IWP, is a novel approach to this problem.…”
Section: Introductionmentioning
confidence: 99%